Teachers as Drivers of Islamic Experience: An Innovative Approach to Islamic Religious Education Learning - Nur Cahyati; Juliani; Nuriyani; M. Arfinal; Muhammad Fahmi Harahap (Journal of Contemporary Islamic Primary Education, 2024)
The purpose of this study is to identify the importance of teachers as drivers of Islamic experiences by using or implementing an innovative approach to Islamic Religious Education learning which can ultimately create an Islamic experience with the very important role of teachers in Islamic Religious Education learning is indeed true. This research is included in the category of library research, which is a type of research that prioritizes text analysis and tries to collect research data from various literature sources. The literature used as a reference is journals, E-Books, and other materials. To provide an overview that is in accordance with the purpose of writing this journal, this study also uses a qualitative approach with descriptive methodology. The data collection method used in this study is literature collection, which is the process of collecting library materials that are in accordance with the topic of discussion. Islamic Religious Education Learning, it is very important to innovate Islamic Religious Education learning to increase student learning motivation and improve student thinking levels. So that Islamic Religious Education learning will produce results in everyday life. Because learning Islamic Religious Education is initially boring if using a conventional model that is limited in the classroom, then with the existence of an innovative learning model that can be applied to the subject will encourage students to learn Islamic Religious Education so that an Islamic experience is created.